The implementation of benchmarking process in marketing education services by Ukrainian universities - G.V. Okhrimenko (Marketing i Menedžment Innovacij, 2016)
The aim of the article. The consideration of theoretical and practical aspects of benchmarking at universities is the main task of this research. At first, the researcher identified the essence of benchmarking. It involves comparing the characteristics of college or university leading competitors in the industry and copying of proven designs. Benchmarking tries to eliminate the fundamental problem of comparison – the impossibility of being better than the one from whom they borrow solution. Benchmarking involves, therefore, self-evaluation including systematic collection of data and information with the view to making relevant comparisons of strengths and weaknesses of performance aspects. Benchmarking identifies gaps in performance, seeks new approaches for improvements, monitors progress, reviews benefits and assures adoption of good practices. The results of the analysis. There are five types of benchmarking: internal, competitive, functional, procedural and general. Benchmarking is treated as a process of systematically applied and has specific stages: 1) identification of study object; 2) identification of businesses for comparison; 3) selection of data collection methods; 4) determining variations in terms of efficiency and determination of the levels of future results; 5) communicating of the results of benchmarking; 6) development of implementation plan, initiating the implementation, monitoring implementation; 7) new benchmarks definition. The researcher gave the results of practical use of the benchmarking algorithm at universities. In particular, the monitoring and SWOT-analysis were identified competitive practices used at Ukrainian universities. The main criteria for determining the potential for benchmarking of universities were: 1) the presence of new teaching methods at universities; 2) the involvement of foreign lecturers, partners of other universities for cooperation; 3) promoting education services for target groups; 4) violation of the problems of the introduction of new methods of attracting applicants and partners at conferences or other scientific events. Attracting of the attention of partners and students determined as a priority direction in benchmarking of universities and required some recommendations: a) systematic optimization of university and institution sites (SEO (Search engine optimization), SMO (Social media optimization)); b) contextual and banner advertising of universities educational services (graphics, animation products on different sites); c) guerrilla marketing blogs (Social media marketing); d) systematic implementation of international cooperation with leading universities based on educational platform of electronic and innovative study methods. Conclusions and directions of further researches. Benchmarking has a special place among innovation marketing movements, but first there are other major routes towards quality and improved performance. Quality control augmented with systematic, continual efforts at enhancement or improvement of quality is known as quality management. It is the main task for the leadership structure of higher education institutions.